2015
DOI: 10.1007/s10661-014-4257-9
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of coastal coral reefs near Dahab (Gulf of Aqaba, Red Sea) indicates local eutrophication as potential cause for change in benthic communities

Abstract: Coral reef ecosystems fringing the coastline of Dahab (South Sinai, Egypt) have experienced increasing anthropogenic disturbance as an emergent international tourism destination. Previous reports covering tourism-related impacts on coastal environments, particularly mechanical damage and destructive fishing, have highlighted the vital necessity for regular ecosystem monitoring of coral reefs near Dahab. However, a continuous scientific monitoring programme of permanent survey sites has not been established to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 60 publications
1
32
0
Order By: Relevance
“…High rates of sedimentation and low light levels negatively affect coral survival rates (Rogers, ). The combined effects of anthropogenic sedimentation and nutrient enrichment can severely inhibit coral recruitment and settlement, slow coral recovery, reduce resilience, and eventually induce declines in coral coverage and species richness (Abelson et al, ; Birrell et al, ; Naumann et al, ; Nava & Tamírez‐Herrera, ; Wielgus et al, ; Yeemin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…High rates of sedimentation and low light levels negatively affect coral survival rates (Rogers, ). The combined effects of anthropogenic sedimentation and nutrient enrichment can severely inhibit coral recruitment and settlement, slow coral recovery, reduce resilience, and eventually induce declines in coral coverage and species richness (Abelson et al, ; Birrell et al, ; Naumann et al, ; Nava & Tamírez‐Herrera, ; Wielgus et al, ; Yeemin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, many inshore fringing reefs experience increased sedimentation and nutrient levels in response to fertilizer use and land clearing [10]. Consequently, at certain periods of the year, inorganic nitrogen and phosphorus concentrations can be much higher [16][17][18][19] than the usual levels measured on reefs (less than 0.5 mM for nitrogen [20][21][22], less than 0.1 mM for phosphate [23][24][25]). Furthermore, the geomorphology and the different sources and types of pollution, will also change the abundance of nitrogen sources (nitrate versus ammonium) and the N : P ratios of coastal ecosystems [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Naumann at al. studied the effect of nutrient on coral reefs near Dahab (Gulf of Aqaba, Red Sea) for 3 years monitoring coral reef cover and water measurement for ammonia, phosphate and nitrates and he found that the live hard coral cover declined significantly through these 3 years about 12 % and increased of algal cover at this sites about 57% [40]. The study shows that ammonia, nitrate, nitrate, total phosphorus, silicate and phosphate concentration recorded the highest concentration from 2010 to 2012 while the total nitrogen concentration showed the highest concentration from 1998 to 2000 and 2012.…”
Section: Discussionmentioning
confidence: 99%